Comparing the mechanical properties of the polymer orthodontic bracket materials with the conventional orthodontic bracket materials: A systematic review - Srinidhi Ramasundaram; Dilip Srinivasan; K. Ravi; Davis Devasahayam (Dental Research Journal)
Background: The aim of this study was to compare the mechanical properties of the polymer brackets with metal and ceramic brackets and verify if the polymer brackets could be used clinically. Materials and Methods: A thorough search was conducted in four electronic databases, including Scopus, PubMed, Cochrane, Ovid, and Lilacs, with article selection based on Preferred Reporting Items for Systematic Reviews and Meta-Analysis standards. A computerized search of the database was done from January 1990 to June 2024. Two independent reviewers were involved in study selection, data extraction, and synthesis. Disagreements were resolved by discussion with a third reviewer. The risk of bias was assessed by the quality assessment tool for in vitro studies (QUIN tool). The outcomes measured included permanent deformation, hardness, and torquing capacity. Results: Ten studies were selected after excluding duplicates, screening, and complete text reading to identify the articles that met the eligibility criteria. All ten studies showed medium risk based on the quality assessment tool for in vitro studies (QUIN Tool). Conclusion: The following findings were obtained: Polymer brackets have lower mechanical properties in terms of torque loss, fracture resistance, hardness, and torsional creep compared to metal brackets. Among the polymers listed in the studies, it was found that polyamide exhibited low hardness and polyoxymethylene exhibited the highest torque loss. Torque deformation was highest with a ceramic-reinforced polymer bracket, followed by pure polymer. Torque deformation was minimal with metal slot- and ceramic-reinforced polymers, followed by metal slot-reinforced polymers.